2006
DOI: 10.1103/physrevb.73.075313
|View full text |Cite
|
Sign up to set email alerts
|

Spin tunneling through an indirect barrier: Tight-binding calculations

Abstract: The present results suggest that large spin polarization can be obtained for energy windows that exceed significantly the spin splitting. The width of these energy windows are mainly determined by the energy difference between the resonance and its associated zero, which in turn, increases with the decrease of barrier transmissibility at direct tunneling.We formulate two conditions that are necessary for the existence of energy windows with large polarization: First, the resonances must be well separated such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In the 3D case, such calculations were recently carried out for some specific materials and qualitatively new features were found. 14,15,16 2D tunnel structures are scantily studied to date. In particular, as far as we know, even the complex band structure of 2D electrons was not explored.…”
Section: Introductionmentioning
confidence: 99%
“…In the 3D case, such calculations were recently carried out for some specific materials and qualitatively new features were found. 14,15,16 2D tunnel structures are scantily studied to date. In particular, as far as we know, even the complex band structure of 2D electrons was not explored.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] Such sharp dips (antiresonance states) are specific to the interferometric nature of the scattering and do not occur in conventional one-dimensional scattering problems of potential barriers. This may be due to the interference between two channels.…”
Section: Calculated Results and Discussionmentioning
confidence: 99%
“…In their work, the authors considered the electrons close to the top of the indirect barrier, where the indirect tunneling becomes dominant [2]. In our previous work [3] we have shown that, at these energies, the Γ-X mixing plays a greater role than Mishra et al suggested [2]. We have also considered the Fano resonances that occur because of the interaction between the discrete states at the X point in the barrier and the continuum at the Γ point in the contacts.…”
mentioning
confidence: 99%
“…The zero in the transmission occurs whenever the amplitude magnitudes of the two channels become equal. In our previous paper [3] we have used a realistic empirical tight binding model to give a unified description of the spin dependent tunneling through an indirect symmetric barrier with the GaAs/AlAs/GaAs heterostructure as an example. We showed several interesting aspects of such process, with particular emphasis on the large energy windows of spin polarization that can be obtained when appropriate conditions are satisfied.…”
mentioning
confidence: 99%
See 1 more Smart Citation